Brazilian guidelines for diagnosis, treatment and follow-up of primary cutaneous melanoma - Part II - Luiz Guilherme Martins Castro; Renato Marchiori Bakos; João Pedreira Duprat Neto; Flávia Vasques Bittencourt; Thais Helena Bello Di Giacomo; Sérgio Schrader Serpa; Maria Cristina de Lorenzo Messina; Walter Refkalefsky Loureiro; Ricardo Silvestre e Silva Macarenco; Hamilton Ometto Stolf; Gabriel Gontijo (Sociedade Brasileira de Dermatologia, 2016)
Abstract The last Brazilian guidelines on melanoma were published in 2002. Development in diagnosis and treatment made updating necessary. The coordinators elaborated ten clinical questions, based on PICO system. A Medline search, according to specific MeSH terms for each of the 10 questions was performed and articles selected were classified from A to D according to level of scientific evidence. Based on the results, recommendations were defined and classified according to scientific strength. The present Guidelines were divided in two parts for editorial and publication reasons. In this second part, the following clinical questions were answered: 1) which patients with primary cutaneous melanoma benefit from sentinel lymph node biopsy? 2) Follow-up with body mapping is indicated for which patients? 3) Is preventive excision of acral nevi beneficious to patients? 4) Is preventive excision of giant congenital nevi beneficious to patients? 5) How should stages 0 and I primary cutaneous melanoma patients be followed?